Principals’ Perceived Effect of Conflict Resolution Procedures on Teachers' Job Satisfaction: A Case Study in Government Technical Colleges of Kano State, Nigeria - Isaac John Ibanga; Idris Mustapha Abdullahi; Garba Zakariya’u (Journal of Pedagogy and Education Science, 2023)
The study aimed to investigate the impact of conflict resolution procedures on teachers' job satisfaction in Government Technical Colleges in Kano State, Nigeria. The population of the study was 367 respondents, including 15 principals and 352 technical teachers. A sample size of 201 respondents was determined using the correlational research design. The instrument used for data collection was a structured questionnaire titled "Principal’s Conflict Resolution Procedure Appraisal Questionnaire (PCRPAQ)." The questionnaire was validated by three experts, and the reliability index obtained using Cronbach Alpha was 0.82. The research questions were answered using the mean and standard deviation, and regression analysis was used to test the null hypotheses at a 0.05 level of significance. The findings of the study revealed that arbitration conflict management strategy and effective communication conflict management strategy had a moderate influence on teachers' job satisfaction. Based on the findings, the study recommends that civil societies should enlighten school administrators, teachers, and teachers' unions about the need to adopt the arbitration conflict management strategy, as the constitution provides for all labor-related cases to be handled at the arbitration court.